Illusions of improvement: aspirations and realities of quality assurance and accreditation policy in Afghanistan higher education. Issue 3 (16th April 2022) - Niroo, Wolayat Tabasum; Glass, Chris R.
ABSTRACT: To enhance the quality of higher education in Afghanistan, the Afghan Ministry of Higher Education (MoHE) adapted quality assurance and accreditation (QAA) policies developed in other countries to the Afghan context. Perspectives on the effectiveness of the new QAA policy have been mixed. On the one hand, the MoHE believes the QAA policy has transformed the Afghan higher education system. On the other hand, the faculty and administrators charged with implementation have expressed concerns about government inspection and control, lack of resources to improvements, and worries that the policy is an impartation of Western countries. This study explored the gap between QAA policy reform efforts by the MoHE and implementing these efforts at Afghan universities. The findings highlight conflicting views of whether QAA policy was an authentically Afghan-led process, practical issues with Afghan universities' capacity to implement QAA policy, and whether the reality of the QAA policy met aspirations for improved educational quality. This study adds to the knowledge of quality assurance and accreditation by exploring the tensions and complexities in implementing a Western QAA model in developing countries like Afghanistan. We pay particular attention to the ethical dimensions of quality assurance implementation in post-conflict countries.